Nonlinear finite element analysis of electromechanical behaviors in a piezoelectric semiconductor beam - Han, C.; Lu, Chunsheng; Zhao, M.; Zhang, Q. (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
In this paper, a one-dimensional beam model with extensional, flexure and shearing deformations for a piezoelectric semiconductor fiber is established based on the first-order beam theory and nonlinear electric current constitutive relation. To solve such a nonlinear beam model under transverse and axial forces, a finite element method is proposed together with an iterative process. Throughout numerical case studies, effects of the external forces and initial electron concentration are investigated on electromechanical fields. It is shown that the applied forces have a great influence on the distribution of electron concentration, which can freely regulate the electron transport in piezoelectric semiconductors.